2021
DOI: 10.1101/2021.02.23.432472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic incompatibilities do not snowball in a demographic model of speciation

Abstract: Two populations evolving in isolation can accumulate genetic differences over time that cause incompatibilities in their hybrid offspring. These “Dobzhansky-Muller incompatibilities” (DMIs) are predicted to accumulate at a rate faster than linear as the number of incompatible gene interactions “snowballs”. Here we show that this snowball prediction is an artifact of two unrealistic modeling assumptions that stem from ignoring demography. We introduce a new alternative “demographic speciation model” in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Data consistent with this phenomenon has been documented in several systems ( Matute et al, 2010 ; Moyle and Nakazato, 2010 ; Wang et al, 2015 ). However, if the mutations that cause DMIs are enriched in the same genes or genomic regions, the rate of this accumulation should slow ( Kalirad and Azevedo, 2017 ; Maya-Lastra and Eaton, 2021 ). Similar predictions emerge from theoretical studies of gene regulatory network evolution, where the likelihood of a gene’s involvement in DMIs is directly related to the density of the gene network ( Yang and Scarpino, 2020 ; Satokangas, 2020 ).…”
Section: Ways Forwardmentioning
confidence: 99%
“…Data consistent with this phenomenon has been documented in several systems ( Matute et al, 2010 ; Moyle and Nakazato, 2010 ; Wang et al, 2015 ). However, if the mutations that cause DMIs are enriched in the same genes or genomic regions, the rate of this accumulation should slow ( Kalirad and Azevedo, 2017 ; Maya-Lastra and Eaton, 2021 ). Similar predictions emerge from theoretical studies of gene regulatory network evolution, where the likelihood of a gene’s involvement in DMIs is directly related to the density of the gene network ( Yang and Scarpino, 2020 ; Satokangas, 2020 ).…”
Section: Ways Forwardmentioning
confidence: 99%
“…They found a significantly negative correlation in one genus, in agreement with our prediction, but no significant correlations in the other two genera. A larger phylogenetic study found significant negative correlations between speciation rates and a different proxy for N e —geographic range size—in both birds and mammals 52 . These results, while encouraging, have the limitation that they have used overall speciation rate, which may not be driven primarily by postzygotic RI.…”
Section: Discussionmentioning
confidence: 96%
“…for N e -geographic range size-in both birds and mammals 52 . These results, while encouraging, have the limitation that they have used overall speciation rate, which may not be driven primarily by postzygotic RI.…”
Section: Discussionmentioning
confidence: 99%
“…The phase during which BDMi mutations emerge, spread through the population and eventually get fixed is often dismissed ( e.g ., [ 42 ]). This necessary phase has recently been argued to have important implications in speciation genetics [ 63 , 64 ]. Considering that BDMi alleles may segregate in natural populations at polymorphic frequencies allows for instance to better explain (i) why hybrid incompatibility may be variable between different pairs of individuals originating from the same two populations (reviewed in [ 63 ]), and (ii) why genetic incompatibilities are widespread within species, as found in Drosophila melanogaster [ 65 ], Caenorhabditis elegans [ 66 ], Arabidopsis thaliana [ 67 ], or the genus Draba [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%